Emissão superradiante de 1 e 2 fótons por uma memória quântica de átomos frios - Davi de Freitas Barros (2020)
In this work, we consider a quantum memory formed by an ensemble of 3-level atoms to study the emission of light in a Fock state for one and two excitations, exhibiting the superradiant character in these processes. In this setup, a writing laser beam may induce quantum transitions between pairs of levels, leaving either one or two of these atoms excited in an appropriate coherently distributed state across the cloud, thus storing quantum information. After that, a reading laser beam extracts this information in the form of one or two photons, respectively, in a superradiant emission at a specific mode of the electromagnetic field that depends on the details of the stored state. Then, we can certify the quantum nature of light, making sure that a semi-classical approach is inadequate to describe this phenomenon. The central point is the development of an analytical theory for the interaction between atoms and light in this context. We find the beam’s spatio-temporal profile, showing that the modes in which the generated read and write photons are counterpropagating. Following the theory, the two-photon wavepacket is consistent with the profile obtained for two independent photons, each identical to the one achieved for a single superradiant emission. These conclusions match with experimental studies of quantum information storage by a cloud of cold atoms realized by the quantum optics group at UFPE, where we notice a good agreement between theory and experiment. These studies allowed the first characterizations of the superradiant emission of two photons by an atomic ensemble.